CULTIVATING EXCELLENCE IN THE ART OF DANCE: AN IN-DEPTH STUDY OF TEACHING STRATEGIES FOR THE COMPREHENSIVE DEVELOPMENT OF THE ART OF DANCE IN HIGHER EDUCATION - Sui Pengying, Fan Mingde (Chelonian Research Foundation, 2023)
In the context of the higher education, dance serves as an art form, which complements artistic expression, physical prowess and cultural relevance. Dance teachers rely on different strategies in order to cultivate excellence in dance within higher education institutions. This study delves into the review of teaching strategies, which promote the holistic success of dance students in higher education. It also focuses on the multidimensional landscape of dance education, shedding light on the cultivation of creativity. By assessing the teaching strategies employed, this research seeks to offer a direction for dance educators traversing the intricate journey of supporting the next generation of dance artists.